The projects' documentation of 'Obra Sindical del Hogar (OHS)' and 'Obra Sindical de Educación y Descanso (EyD)' in the province of Badajoz - Sanz Caballero, Isabel María; Vivas Moreno, Agustín (Revista General de Información y Documentación, 2020)
The objective of the present work is to make known the importance of the documentation generated by the Spanish Trade Union Organization, focusing on the "Trade Union Works of the Home" and the "Trade Union Works of the Education and Rest". During the Franco Dictatorship, both the "Trade Union Works of the Home" and the "Trade Union Works of the Education and Rest" (EyD) together with the "Vocational Training Works" were the ones with the highest budget. According to data from the "Spanish Sindical Works" itself, a total of 138,686 homes were created. These data translate into the appearance of a large amount of documentation produced by these organizations during these years, which means a substantial fund that allows us to know how housing projects were executed, the procedures to be followed, the technical conditions, the qualities of which they were available, the beneficiaries of these houses, who promoted the houses and the expropriations that were realized. The methodology followed to achieve the objectives of the study, has been triple, on the one hand, an institutional methodology has been followed, in order to analyze the documentary genesis and the identification of the Series, the series description is done using ISAD (G), subsequently, the documentary methodology has been followed, in order to describe more relevant type dossier; and finally, the historical methodology, in order to analyze the historical relevance of the documentation. The analysis of the documentation conserved in the Archive of the Territorial Service of Badajoz will allow to make known the type of construction projects carried out during the Franco Dictatorship stage in the Badajoz province, as well as the context in which they were carried out.
Keywords: fonds; Franco dictatorship; trade union works; housing; Badajoz